Halal Discourse in Indonesia: Politicization of al-Qur'an-Hadith Interpretation and Business Strategy - Muqtada, Muhammad Rikza (HERMENEUTIK : Jurnal Ilmu al-Qur'an dan Tafsir, 2023)
This article shows how business people and consumers understand and practice the halal concept. The concept of halal, understood only based on the narrative of the Qur’an and hadith, turns out to be more complex at the practical level because it involves market behavior and contains elements of religious politicization. Using a living tradition approach, this qualitative research reveals the reciprocal relationship between religious texts and community practices, social context, and performative actions by halal business actors in the districts of Semarang and Salatiga City, Indonesia. The results show that 1) halal business behaviors are a form of embodiment of Muslim business people's interpretation of the essence of the teachings of the Qur’an and hadith, which are understood textually on business platforms. 2) This halal business movement emerged as a response to (a) global market trends which are starting to target consumers who are experiencing increased religiosity and spirituality, (b) modern capitalism, which is starting to touch religious areas, starting from production, business systems, to marketing, and 3) political developments global economy that makes halal a business commodity. Thus, the theoretical contribution of this paper is that the concept of halal cannot be defined only based on the interpretation of the Qur’an or the interpretation of hadith but is closely related to traditional practices in the field, which involve market behavior and trade politics.Diskursus Halal di Indonesia: Politisasi Tafsir al-Qur'an-Hadis dan Strategi Bisnis. Tulisan ini menunjukkan bagaimana konsep halal itu dipahami dan dipraktikkan oleh para pelaku bisnis dan konsumen. Konsep halal yang selama ini dipahami hanya berdasarkan narasi al-Qur’an dan hadis, ternyata konsep tersebut lebih kompleks dalam tataran praktiknya, karena melibatkan perilaku pasar serta mengandung unsur politisasi agama. Dengan pendekatan living tradition, penelitian kualitatif ini mengungkap hubungan resiprokal antara teks agama dengan praktik Masyarakat, konteks sosial serta tindakan performatif yang dilakukan oleh para pelaku bisnis halal di Kab. Semarang dan Kota Salatiga Indonesia. Hasil menunjukkan bahwa perilaku bisnis halal adalah bentuk pengejawantahan dari penafsiran para pebisnis Muslim atas intisari ajaran al-Qur’an dan hadis yang dipahami secara tekstual dalam platform bisnis. Gerakan bisnis halal ini bangkit sebagai respon atas: a) trend pasar global yang mulai membidik konsumen yang mengalami peningkatan religiusitas dan spiritualitasnya, b) kapitalisme modern yang mulai menyentuh wilayah religious, mulai dari produksi, sistem bisnis, hingga pemasarannya, dan 3) perkembangan politik ekonomi global yang menjadikan halal sebagai komoditas bisnis. Dengan demikian, kontribusi teoretik tulisan ini adalah bahwa konsep halal tidak bisa didefinisikan hanya berdasarkan penafsiran al-Qur’an maupun interpretasi hadis, namun erat kaitannya dengan praktik tradisi di lapangan yang melibatkan perilaku pasar dan politik dagang.